Factors influencing the sexuality education among students in Poland – a survey study - Halczuk, Aleksandra; Sieńko, Anna; Kowalczuk, Dorota (Journal of Education, Health and Sport, 2019)
Introduction: Sex education is commonly associated with preventing consequences of lack of knowledge in field of sexuality such as unintended pregnancy or sexually transmitted diseases (STDs). However, when well designed and introduced it enables children to better understand sexuality as an integral part of human nature, allows defining one’s own sexuality, teaches about relationship building and raises awareness of consequences of irresponsible sexual behaviour. The aim of the study: The presented study was aimed at assessing of sexuality education quality among students in Poland and factors influencing this process. Material and methods: The analysed material was obtained on the basis of a survey conducted on group of young adults, especially medical students. Standardized questionnaire consisting of 35 questions divided into three parts (first part – general information about participants, second part – sexual activity, contraception and sources of knowledge about them, third part – simple questions verifying the knowledge of participants) has been shared in social media via Google Forms. Results: 200 participants filled the entire questionnaire (149 female and 51 male). The survey indicates that: 75% of respondents were under 25 years old; the vast majority (96%) of participants were medical students; 37,5% of participants described themselves as practicing believers which correlated with sexual initiation at the age of 20 or later; 41,5% of respondents uses physical barrier contraceptives combined with natural methods although they consider hormone-based methods combined with barrier methods as the most appropriate for them (40,5%); level of parent education and employment in medical professions were not associated with the presence and the quality of family sex education; majority of participants indicated the Internet, school or university as main information sources about topics related to sexuality; the most participants (47,5%) expressed the opinion that parents should be the most appropriate source of knowledge about human sexuality. No one chose the Internet as an appropriate source of sex education. Conclusion: The conducted survey suggests that many young people lack basic knowledge about sexuality and contraception.